Molecular characterization and expression analysis of protein enhancer of sevenless 2B from Artemia sinica at early embryonic development and during immune response to bacterial stimulation. Issue 87 (April 2019) - Xia, Yu; He, Kang; Jiao, Lili; Geng, Yuanyuan; Zhang, Daochuan
Abstract: Protein enhancer of sevenless 2B, E(sev)2B, is a key adapter protein in the Ras/MAPK signaling pathway which has been reported to be involved in innate immunity. In this study, the gene that encodes As E(sev)2B was isolated from A. sinica. It was found to contain a 636 bp open reading frame encoding 211 amino acids with a calculated molecular mass of 24.357 kDa and a predicted isoelectric point of 5.39. The predicted protein contains a N-terminal Src homology 3 domain (SH3), a central Src homology 2 domain (SH2), and a C-terminal Src homology 3 domain (SH3). Homology analysis revealed that As E(sev)2B shares 49%–95% identity with E(sev)2B homologs from other species. In this study, the expression pattern and location of As E(sev)2B during different stages of embryonic development and bacterial challenge were investigated by means of real-time qPCR, Western blotting and immunohistochemistry. Results showed that the highest expression level of As E(sev)2B was at 0 h. After challenged by Gram-positive bacteria and Gram-negative bacteria, As E(sev)2B was remarkably upregulated at 10 6 cellsL −1 bacterial concentrations. These results suggested that As E(sev)2B plays a vital role during early embryonic development and in immune responses against bacterial challenge. Highlights: Open reading frame of E(sev)2B was isolated and characterized from Artemia sinica. As E(sev)2B was expressed at all developmental stages using RT-qPCR and Western blotting. The signals of As E(sev)2B were mainly detected in the cephalothorax by immunohistochemistry. As E(sev)2B was remarkably upregulated under stimulated by Gram-positive and Gram-negative bacteria.